2004
DOI: 10.1097/01.phm.0000107497.77487.c1
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Disability in Survivors of Multiple Trauma One Year After Intensive Care Unit Discharge

Abstract: The majority of survivors of major trauma exhibit considerable levels of disability and impairment in health-related quality of life. Global injury severity score and degree of brain trauma determine functional limitations. This information may help in organizing long-term rehabilitation of multiple-trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 24 publications
7
54
0
1
Order By: Relevance
“…In the present study 49 (45%) of the patients were on sick leave six months after the trauma, which declined to 18 (17%) at 24 months. Other studies have shown that 36%-47% of their patients were unable to work 12 months after the trauma, (34,35) and about 20% for up to five years after the trauma. (28,32), 30 These data support the fact that our trauma group does not seem to be significantly different in these aspects 18 in comparisons of HRQoL from other patients in ICU and control groups.…”
Section: Pre-existing Diseasementioning
confidence: 99%
“…In the present study 49 (45%) of the patients were on sick leave six months after the trauma, which declined to 18 (17%) at 24 months. Other studies have shown that 36%-47% of their patients were unable to work 12 months after the trauma, (34,35) and about 20% for up to five years after the trauma. (28,32), 30 These data support the fact that our trauma group does not seem to be significantly different in these aspects 18 in comparisons of HRQoL from other patients in ICU and control groups.…”
Section: Pre-existing Diseasementioning
confidence: 99%
“…N eurological deficits are a common consequence of head trauma producing traumatic brain injury (TBI) (Annoni et al, 1992;Dimopoulou et al, 2004;Jennett et al, 1981), with hemiparesis, aphasia, and cranial nerve dysfunction contributing substantially to overall outcome of severe TBI. In fact, Jennett and Bond ( Jennett and Bond, 1975), the creators of the most commonly used measure of outcome in TBI, the Glasgow Outcome Scale (GOS), indicated that neurological status via a neurophysical assessment should be considered in grading the GOS, since neurophysical deficits contributed significantly to disability in about a third of patients sustaining severe TBI.…”
Section: Introductionmentioning
confidence: 99%
“…The main injury severity factor was the ISS as it has previously been shown to be a good predictor of outcome after trauma [14,[18][19][20]. Other measures of injury severity were: presence of a neck injury (defined as a cervical spine fracture or dislocation/subluxation on presentation), presence of a significant head injury (an Abbreviated Injury Scale [21] of 3 or higher), admission to intensive care, and days spent in intensive care.…”
Section: Methodsmentioning
confidence: 99%